NARASI LOKAL DAN MEMORI KOLEKTIF PEMBERONTAKAN KAHAR MUZAKKAR: STUDI KOMPARATIF PERSPEKTIF MASYARAKAT JENEPONTO DAN TAKALAR - Nurul Musrifah; Irwansyah Irwansyah; Fauziah Fauziah; Nur Ika Sari; Serlina Febrianti; Said Hanafi; A. Tenri Rama Devi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The Abdul Qahhar Mudzakkar movement represents one of the most significant historical events in South Sulawesi, leaving diverse memories among communities across different regions. This study aims to analyze the production and reproduction of collective memory regarding the movement through a comparative study of communities in Jeneponto Regency and Takalar Regency. The research employed a qualitative approach with a comparative case study design grounded in the constructivist-interpretivist paradigm. Data were collected through oral history interviews with community leaders, historical actors, and subsequent generations who inherited narratives about the DI/TII movement, supported by relevant literature and historical documents. The research process involved data collection, data reduction, thematic categorization, narrative interpretation, and comparison of collective memory constructions across the two regions. The findings reveal that collective memory of Abdul Qahhar Mudzakkar is not singular but is shaped by social experiences, generational positions, and local contexts. The people of Jeneponto Regency tend to portray Kahar as a rebel associated with violence and social suffering, whereas the people of Takalar Regency exhibit a more ambivalent memory characterized by a combination of fear and sympathy influenced by narratives of religious struggle. Furthermore, experiences of pressure from both the DI/TII movement and state security forces contributed to the formation of collective trauma transmitted across generations. This study concludes that remembrance, forgetting, and the reproduction of historical narratives are products of dynamic social construction. The novelty of this research lies in its comparative analysis of collective memory in two regions with distinct historical experiences, thereby contributing to the development of collective memory and oral history studies within the context of Indonesian local history. ABSTRAK Gerakan Abdul Qahhar Mudzakkar merupakan salah satu peristiwa penting dalam sejarah Sulawesi Selatan yang meninggalkan jejak memori yang berbeda pada masyarakat di berbagai wilayah. Penelitian ini bertujuan menganalisis produksi dan reproduksi memori kolektif masyarakat terhadap gerakan tersebut melalui studi komparatif di Kabupaten Jeneponto dan Kabupaten Takalar. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus komparatif berlandaskan paradigma konstruktivis-interpretivis. Data dikumpulkan melalui wawancara sejarah lisan terhadap tokoh masyarakat, pelaku sejarah, dan generasi penerus yang mewarisi narasi tentang gerakan DI/TII, serta didukung kajian literatur dan dokumen historis. Tahapan penelitian meliputi pengumpulan data, reduksi data, kategorisasi tema, interpretasi narasi, dan perbandingan konstruksi memori pada kedua wilayah. Hasil penelitian menunjukkan bahwa memori kolektif mengenai Abdul Qahhar Mudzakkar tidak bersifat tunggal, melainkan dibentuk oleh pengalaman sosial, posisi generasi, dan konteks lokal. Masyarakat Kabupaten Jeneponto cenderung merepresentasikan Kahar sebagai pemberontak yang identik dengan kekerasan dan penderitaan sosial, sedangkan masyarakat Kabupaten Takalar menampilkan memori yang lebih ambivalen karena adanya perpaduan antara rasa takut dan simpati yang dipengaruhi narasi perjuangan berbasis agama. Selain itu, pengalaman tekanan dari kelompok DI/TII maupun aparat negara membentuk trauma kolektif yang diwariskan antargenerasi. Penelitian ini menyimpulkan bahwa ingatan, pelupaan, dan reproduksi narasi sejarah merupakan hasil konstruksi sosial yang dinamis. Kebaruan penelitian terletak pada analisis komparatif memori kolektif di dua wilayah dengan pengalaman historis berbeda, sehingga memperkaya kajian memori kolektif dan sejarah lisan dalam konteks sejarah lokal Indonesia.